2007
DOI: 10.1158/0008-5472.can-06-2037
|View full text |Cite
|
Sign up to set email alerts
|

p53 Enhances Gefitinib-Induced Growth Inhibition and Apoptosis by Regulation of Fas in Non–Small Cell Lung Cancer

Abstract: Treatment with gefitinib, a specific inhibitor of epidermal growth factor receptor tyrosine kinase (EGFR-TK), has resulted in dramatic responses in some patients with nonsmall cell lung cancer (NSCLC). Most patients who respond to gefitinib have EGFR-TK mutations; however, >10% of patients with EGFR-TK mutations do not respond. Similarly, some patients without EGFR-TK mutations respond to this drug, suggesting that other factors determine sensitivity to gefitinib. Aberrations of the tumor suppressor gene p53 a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 38 publications
4
82
1
Order By: Relevance
“…Restoration of p53 to p53-defective H1299 cells can enhance the sensitivity to gefitinib (35). In the present study, the resistant of H1299 cells to gefitinib could not be reversed by the ectopic overexpression of HER2.…”
Section: Discussioncontrasting
confidence: 44%
“…Restoration of p53 to p53-defective H1299 cells can enhance the sensitivity to gefitinib (35). In the present study, the resistant of H1299 cells to gefitinib could not be reversed by the ectopic overexpression of HER2.…”
Section: Discussioncontrasting
confidence: 44%
“…9 Recent data showed that sensitivity to gefitinib is affected by P53 mutation and that P53 inhibition induces a significant decrease in apoptosis induction by gefitinib. 10 Previous study already demonstrated that cetuximab inhibited the growth of wild-type p53 but not of mutated p53 cancer cells and hypothesized that resistance to cetuximab could relate to p53 mutation. 11 In addition, recent study showed that induction of P53 resulted in decreased in phosphorylated AKT activity in cell line, which did not express PTEN protein, thus highlighting that p53 was involved in regulation of survival PI3K/AKT pathway in epithelial tumors, and independently of PTEN expression.…”
Section: Introductionmentioning
confidence: 99%
“…Aberrations of p53 are usually associated with drug resistance. Recent data showed that human urothelial cells with loss of p53 function displayed reduced sensitivity to TKIs (27) and p53 is required for maximal sensitivity to gefitinib-induced apoptosis in non-small cell lung cancer (28). One point mutation (codon 135, cysteine to serine) was identified in the UM-UC-14 cells (data not shown).…”
Section: Discussionmentioning
confidence: 98%